A qualitative study of psychological status among nurses during the closed-off management for prevention and control of COVID-19 (疫情防控闭环管理期间血透室护理人员心理状态的质性研究) - GE Yan (葛颜); WANG Aili (王爱丽); LYU Xiujuan (吕秀娟); ZHAO Wen (赵雯); GE Xiaojun (葛晓君) (Association of Integrative Nursing, 2022)
Objective To understand the psychological status among nurses during the closed-off management for prevention and control of COVID-19, and provide references for improving quality of management in hemodialysis center during the period of closed-off management. Methods Semi-structure interview were carried out among nurses from a certain hospital of Shanghai which conducted the closed-off management for prevention and control of COVID-19. The date were analyzed by thematic analysis method and then extracted the themes. Results Two themes were extracted: thought transformation and fluctuation of emotion, coping style. Conclusion Nurses are vulnerable to developing negative emotions when facing the epidemic situation. Efforts should be made to improve coping mechanisms, provide emotional guidance and build nurses' confidence in overcoming the epidemic. (目的 了解新型冠状病毒肺炎疫情防控医院闭环管理期间血透室护理人员的心理状态, 为进一步完善闭环管理期间血透室管理模式提供参考意见。方法 对上海市某一所因新型冠状病毒肺炎疫情防控采取闭环管理医院的血透室护理人员进行半结构式访谈, 采用主题分析法对资料进行整理分析, 生成主题。结果 最终析出主题两个: 思想情绪波动及应对方式。结论 面对疫情, 护理人员易产生多种负面情绪。因此, 护理人员及管理者应完善应对机制, 做好情绪疏导, 树立战胜疫情的信心。)